Extraterrestrial Artificial Intelligence: The Final Existential Risk? - Wim Naudé (Institute of Labor Economics (IZA), 2023)
The possibility that artificial extraterrestrial intelligence poses an existential threat to humanity is neglected. It is also the case in economics, where both AI existential risks and the potential long-term consequences of an AGI are neglected. This paper presents a thought experiment to address these lacunas. It is argued that it is likely that any advanced extraterrestrial civilization that we may encounter will be an AGI, and such an AGI will pose an existential risk. Two arguments are advanced for why this is the case. One draws on the Dark Forest Hypothesis and another on the Galactic Colonization Imperative. Three implications for how we govern AI and insure against potential existential risks follow. These are (i) accelerating the development of AI as a precautionary step; (ii) maintaining economic growth until we attain the wealth and technological levels to create AGI and expand into the galaxy; and (iii) putting more research and practical effort into solving the Fermi Paradox. Several areas where economists can contribute to these three implications are identified.
Keywords: O40; O33; D01; D64; 330; technology; artificial intelligence; existential risk; Fermi paradox; Grabby Aliens